REVITALIZING ISLAMIC LIBERATION THEOLOGY ACCORDING TO ASGHAR ALI ENGINER: INSIGHTS INTO HUMAN EQUALITY, GENDER INJUSTICE, AND ECONOMIC INEQUALITY - Alif Jilham Kusuma Putra (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
This research aims to obtain an overview of the concept of Islamic liberation theology according to Asghar Ali Enginer. The method used in this research is a descriptive library research method, which means that researchers examine the results of the literature in the form of book studies or recent journals regarding the concept of Islamic liberation theology by Asghar Ali Enginer, the findings of which researchers examine or explore, then describe in a scientific article study. The findings obtained by researchers regarding the concept are that Asghar Ali Enginer is a da'i, human rights activist, social activist, teacher, and writer. At least, there are three major problems that concern Asghar Ali Enginer in realizing the project of revitalizing Islamic liberation theology, namely the problem of human equality, the problem of gender injustice, the problem of economic inequality. The main concept of Enginer's idea is to humanize human beings. Responsibility or concern among humans to look right - left, care for the environment or the surrounding area, lend a hand to those in need and avoid being greedy / greedy for wealth so that a peaceful and prosperous society can be created.